Social competence and observer-rated social functioning in bipolar disorder - Depp, Colin A (2010)
OBJECTIVE: Impairment in social functioning appears to be common in bipolar disorder, although estimates have been derived largely from self-report measures. We examined performance-based and observer-based ratings of social competence and functioning and assessed the contribution of symptoms and neurocognitive ability to social functioning in bipolar disorder. METHODS: In this cross-sectional study, 164 subjects with bipolar disorder were administered the performance-based Social Skills Performance Assessment (SSPA), rated by an informant on the Specific Level of Functioning (SLOF)–Interpersonal subscale, received clinical ratings of depression and manic symptoms, and performed neurocognitive tests. We assessed the proportion of patients exhibiting social deficits and examined the associations between composite measures of neurocognitive ability, depression and manic symptoms, and SSPA scores with informant-rated, real-world social functioning. RESULTS: Mean age of the sample was 47.6 years (SD = 14.1). Subjects were experiencing, on average, mild levels of depression and minimal manic symptoms. A total of 29% exhibited norm-referenced impairment on the SSPA, and 64% registered at least one impairment on SLOF items; unemployed subjects had lower SSPA and SLOF ratings. Neurocognitive performance correlated with both performance-based and observer-rated social functioning, whereas depressive and manic symptoms correlated only with observer-rated social impairments. In multivariate models, depression was the most potent association with social functioning, and impairment in social competence (i.e., capacity) increased the strength of the relationships between depression and neurocognitive impairment and social functioning (i.e., real-world functioning). CONCLUSIONS: Our study confirmed the negative relationship of bipolar depression with social functioning. A subgroup of outpatients with bipolar disorder has impaired social competence, which, when present, worsened the impact of depression and cognitive impairment on social functioning.